Importance of considering depression for diabetes self-management (Boletín Semillero de Investigación en Familia, 2024)
Introduction: there is evidence of a bidirectional association between depression and diabetes. The causes of depression in people with diabetes are not well understood, however, the mechanisms that trigger it include biological, behavioral, social, psychological and environmental factors and directly influence self-management. This highlights the need for the health professional to collaborate with the person living with type 2 diabetes at risk of developing depression, so that they have access to adequate and timely treatment, to improve and maintain self-management of their disease.Objectives: to reflect on the importance of considering depression in the self-management of people living with type 2 diabetes.Conclusion: self-management is essential to avoid the complications of diabetes, and it has been proven that optimal self-management also reduces the risk of developing mental health disorders, mainly because people are able to manage the disease effectively, seeking all possible help and establishing improvement in their treatment.
Keywords: depression; mental health; self-management; diabetes mellitus